Estudo químico e avaliação da atividade antiinflamatória, antimicrobiana, antioxidante e moluscicida de Ficus radicans Variegata - Naressi, Maria Augusta (2009)
The Ficus radicans Variegate species belongs to the Moracea family and genus Ficus, which includes approximately 800 species and occurs in tropical and subtropical regions. In review of literature, no chemical study of species Ficus radicans Variegata was found. This work aims the chemical study of Ficus radicans Variegata and evaluation of anti-inflammatory, antimicrobial, antioxidant and molluscicide activities of methanol crude extract and of its fractions. The chemical study of Ficus radicans Variegata (leaves) resulted, after purification and fractionation of fractions by using chromatographic methods, in isolation and identification of coumarins: 7-methoxycoumarin (FR-1), 7-hydroxy-6-methoxy-coumarin (FR-4) and 7-methoxy-3,4-dihidrocoumarin (FR-5), steroids: 3-O-β-glucopyranosyl sitosterol (FR-2) and β-sitosterol (FR-3), of trans-4-β-Dglucopyranosyloxy-2-methoxy cinnamic acid (FR-6) and of quercetin 3-O-[β-Dxylopyranosyl-(1→2)-α-L-rhamnopyranoside] (FR-7). The substances structures were proposed on the basis of their spectroscopic data of 1H and 13C NMR, COSY, DEPT, HMQC, HMBC, NOE and NOESY, as well as, comparison with data obtained from the literature. The isolation of substance 7-methoxy-3,4-dihidrocoumarin (FR-5) in plants has not been reported in literature yet. Biological assays were carried out for the crude methanol extract and for its hexane, ethyl acetate and hydromethanol fractions. Antioxidant activity potentials were determined based on scavenging activity of free radical 1,1-diphenyl-2-picrylhydrazyl (DPPH) and showed moderate activity for ethyl acetate fraction (IC50 = 66.19 μg/ml). To evaluate the antibacterial and antifungal activities was used the method of microdilution and strains of bacteria Staphylococcus aureus ATTCC 25923, Escherichia coli ATCC 25922 and Bacillus subtilis ATCC 6623 and the fungus Candida albicans. The tests showed values greater than 1000 μg/ml for minimum inhibitory concentration (MIC) for crude methanol extract and its fractions. Biological tests to evaluate the anti-inflammatory activity, using the edema model of in rats paw induced by carrageenan, showed that the methanol crude extract and fractions hexane and hydromethanol resulted in an inflammatory response reduction when compared to the control group. In the edema ear induced by croton oil model the methanol crude extract an fractions showed a significant reduction of inflammation. The application of the substance 7-methoxycoumarin did not cause significant reduction in edema ear in rats. In the assay for evaluation of molluscicide activity against Biomphalaria glabrata snails, only hexane fraction presented a weak activity.